Lauriana Ren & Qin, a new genus of the tribe Tropidocephalini (Hemiptera: Fulgoromorpha: Delphacidae) from China - Ren, Feng-Juan; Zheng, Li-Fang; Huang, Yi-Xin; Qin, Dao-Zheng (Zootaxa, 2014)
A new delphacid genus and species, Lauriana senticosa Ren & Qin, gen. et sp. nov. (Hemiptera: Delphacidae: Tropidocephalini) is described from Sichuan, China. Habitus photos and illustrations of male genitalia of the new species are given, and the differences between the new genus and its closely related genera are discussed.